2015
DOI: 10.2151/jmsj.2015-041
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal Variability and Seasonal March of the Moist Static Energy Budget over the Eastern Maritime Continent during CINDY2011/DYNAMO

Abstract: This study analyzes radiosonde observations and other datasets to examine variabil ity in the moist static energy (MSE) budget over the eastern Maritime Continent during the CINDY2011/DYNAMO field campaign of October 2011-March 2012. During this period, five events bearing key characteristics of the Madden-Julian oscillation (MJO) are identified. Our analysis focuses on both these events and longer-term seasonal evolution.On the seasonal time scale, the characteristics of column-integrated MSE budget are diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 67 publications
2
27
0
Order By: Relevance
“…The role of the horizontal advection of the dry air from the subtropics in suppressing convection in the western part of the MJO convection and in pushing the eastward migration of the convective envelope (e.g., Fig. 11b) was argued in previous studies (Maloney and Hartmann 1998;Sugiyama 2009;Maloney 2009;Kim et al 2014), and in the CINDY2011/DYNAMO publications Kerns and Chen 2014a, b;Yokoi and Sobel 2015). The high-frequency effects (i.e., nonlinear transport of moisture associated with high-frequency variability) were quantified as the difference between the 6-hourly (unfiltered) advection terms and those from the 7-day-mean (low-pass filtered) values, averaged within each 7-day forecast (Fig.…”
mentioning
confidence: 57%
“…The role of the horizontal advection of the dry air from the subtropics in suppressing convection in the western part of the MJO convection and in pushing the eastward migration of the convective envelope (e.g., Fig. 11b) was argued in previous studies (Maloney and Hartmann 1998;Sugiyama 2009;Maloney 2009;Kim et al 2014), and in the CINDY2011/DYNAMO publications Kerns and Chen 2014a, b;Yokoi and Sobel 2015). The high-frequency effects (i.e., nonlinear transport of moisture associated with high-frequency variability) were quantified as the difference between the 6-hourly (unfiltered) advection terms and those from the 7-day-mean (low-pass filtered) values, averaged within each 7-day forecast (Fig.…”
mentioning
confidence: 57%
“…One core idea that has made significant headway in the community is that MJO precipitation is regulated primarily by atmospheric moisture, often referred to as moisture mode theory (Adames & Kim, 2016;Raymond & Fuchs, 2009;Sobel & Maloney, 2012, 2013Yu & Neelin, 1994). Adopting this framework, many studies have found that anomalous column-integrated horizontal moist static energy (MSE) or moisture advection is crucial to the systematic eastward propagation of the MJO (e.g., Adames & Wallace, 2015;Andersen & Kuang, 2012;Benedict et al, 2015;Cai et al, 2013;Chikira, 2014;Hsu & Li, 2012;Jiang, 2017;Kim et al, 2014;Kim et al, 2017;Maloney, 2009;Pritchard & Bretherton, 2014), although vertical advection has also been noted for playing a role (Hsu & Li, 2012;Sobel et al, 2014;Wang et al, 2017;Yokoi & Sobel, 2015). In particular, it is the horizontal advection of the seasonal mean moisture by the MJO winds in the lower troposphere that appears to be the most important contributor to total horizontal moisture advection (Adames & Wallace, 2015;Cai et al, 2013;Chikira, 2014;Gonzalez & Jiang, 2017;Hsu & Li, 2012;Jiang, 2017;Kim, 2017;Kim et al, 2017;Nasuno et al, 2015;Wolding et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Straub and Kiladis () and Yang and Ingersoll () proposed that slow eastward propagation of MJO convection can be achieved by the MRG group velocity (∼5 m/s; Wheeler & Kiladis, ), a hypothesis that is consistent with the MJOs multiscale structure (e.g., Nakazawa, ). In contrast, equatorial Kelvin‐Rossby wave couplet dynamics with frictional convergence (e.g., Wang & Rui, ; Wang & Chen, ) and a “moisture mode” theory (e.g., Adames & Kim, ; Raymond & Fuchs, ; Sobel & Maloney, , ) have been proposed to describe qualitative characteristics of MJO propagation (e.g., Adames & Wallace, ; Maloney & Hartmann, ; Yokoi & Sobel, ). However, with their analysis of the idealized simulations by a superparameterized Community Atmospheric Model, Pritchard and Yang () questioned moisture mode views, in which horizontal moisture advection by MJO flows acts on propagation (e.g., Adames & Wallace, ).…”
Section: Introductionmentioning
confidence: 99%